Ação da clorexidina na resistência de união e na atividade antibacteriana de diferentes sistemas adesivos: estudo in vitro - Lima, Bruna Caroline de Oliveira (2017)
Chlorhexidine in recent years has been used in dentistry for the improvement of the hybrid layer and consequently greater durability of direct aesthetic restorations. Thus, the objective of this work can be applied in vitro or the effect of chlorhexidine (CHX) on the adhesive interfaces, through the microshear bond strength test and the antibacterial activity of CHX incorporated to different adhesive systems, after 24 hours and 30 days of immersion in solution distilled water. We selected 150 crowns of bovine incisors divided into three groups: G1: Single Bond Plus adhesive system; G2: Clearfil SE Bond adhesive system; G3: adhesive system AdheSE Primer and Bond. All groups were subdivided according to the incorporation of CHX (n = 5): no CHX, with CHX prior to incorporated with 0.5%, 1.0% and 2.0% CHX. The micro-shear test was performed with half the CP after 24 hours and with another medium for 30 days. Later, the fracture modes were also found. Antibacterial diffusion tests on agar with Streptococcus mutans were performed with the same groups and subgroups. The Bond Strength variable was evaluated between the groups and solutions by means of the Factor Variance Analysis for repeated measurements. However, the variable size of the bacterial halo was submitted to Kruskall - Wallis non - parametric test, both with a significance level of 95%. The qualitative variability of fractures was evaluated through descriptive statistical analysis. The concentrations of CHX with 0.5 and 1% contributed to the increase of bond strength values and the Clearfil SE Bond system had the highest mean values in the microshear bond strength test. The AdheSE Bond adhesive system presents the best results without antibacterial testing with S.mutans.